Peritoneal Dialysis Related Infection – Peritonitis Management and Prevention (Pakistan Journal of Kidney Diseases, 2021)
Peritonitis is one of the major risks of peritoneal dialysis (PD) causing signiﬁcant morbidity and in some instances, mortality. It is one of the principal causes of transfer to hemodialysis (HD).  Peritonitis rates should be audited by units.  The recommended rate by the ISPD is less than 0.5 episodes/year
Keywords: Peritoneal dialysis; peritoninitis; gram positive; staphylococcus; fungal peritonitis; risk factors; prevention; ESKD; Hemodialysis